2011
DOI: 10.1021/ma2008783
|View full text |Cite
|
Sign up to set email alerts
|

In SituReduction of Graphene Oxide in Polymers

Abstract: In situ reduction of graphene oxide (GO) at moderate temperatures within a polymer was observed using differential scanning calorimetry (DSC). Comparison of heats of reduction from DSC data in poly(vinylpyrrolidone), poly(vinyl acetate), and poly(vinylpyrrolidone/vinyl acetate) nanocomposites demonstrates that the polymer chemistry strongly influences the extent of reduction. These results are compared to the time–temperature relationship for GO reduction in air and in dimethylformamide at the same temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 79 publications
8
83
0
Order By: Relevance
“…So the LrGO sheets have following two advantages which are more suitable for improving the electrical conductivity of nanocomposites than the small one: 1) there are less intersheet junctions leading to the high intrinsic electrical conductivity, and 2) the large area is prone to form a continuous electrical conductive network. GO sheets could be reduced in different media such as water [10], ethanol, butanol, and ethylene glycol [11] at a special temperature, and the GO sheets also could be reduced in polymer matrix such as poly (vinylpyrrolidone), poly(vinyl acetate) [12] or polyvinylidene fluoride [13]. Glover et al [12] reported that the GO sheets could be reduced in PVA matrix at the temperature range from 150 to 250°C, and the result of Raman peak shift shown that the C:O ratio is less than 10 after reduction.…”
Section: T N Zhou X D Qi Q Fumentioning
confidence: 99%
See 2 more Smart Citations
“…So the LrGO sheets have following two advantages which are more suitable for improving the electrical conductivity of nanocomposites than the small one: 1) there are less intersheet junctions leading to the high intrinsic electrical conductivity, and 2) the large area is prone to form a continuous electrical conductive network. GO sheets could be reduced in different media such as water [10], ethanol, butanol, and ethylene glycol [11] at a special temperature, and the GO sheets also could be reduced in polymer matrix such as poly (vinylpyrrolidone), poly(vinyl acetate) [12] or polyvinylidene fluoride [13]. Glover et al [12] reported that the GO sheets could be reduced in PVA matrix at the temperature range from 150 to 250°C, and the result of Raman peak shift shown that the C:O ratio is less than 10 after reduction.…”
Section: T N Zhou X D Qi Q Fumentioning
confidence: 99%
“…GO sheets could be reduced in different media such as water [10], ethanol, butanol, and ethylene glycol [11] at a special temperature, and the GO sheets also could be reduced in polymer matrix such as poly (vinylpyrrolidone), poly(vinyl acetate) [12] or polyvinylidene fluoride [13]. Glover et al [12] reported that the GO sheets could be reduced in PVA matrix at the temperature range from 150 to 250°C, and the result of Raman peak shift shown that the C:O ratio is less than 10 after reduction. However, this method can maintain the good dispersion of rGO sheets and get rid of introducing the surfactant agents into polymer matrix [14,15], meanwhile avoids using reducing agents, especially hazardous ones.…”
Section: T N Zhou X D Qi Q Fumentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene is one of the strongest materials found to date [23] and has great potential for improving the mechanical properties of polymers [24][25][26][27][28][29]. Reduced graphene oxides (RGO) are typical graphene materials with slight topological defects in their periodic structures [22].…”
Section: Introductionmentioning
confidence: 99%
“…If the synthesis procedure of the gel is not too sensitive for the environment, in situ reduction methods (i.e. reduction agent added to the initial precursor mixture) may be used [28,29]. An effective way to make RGO containing gel composites is to reduce the already incorporated GO inside the gel matrix [30,31], however the circumstances of the reduction (e.g.…”
Section: Introductionmentioning
confidence: 99%